ASPECTUL ECOLOGIC AL IERBURILOR PERENE PENTRU MENŢINEREA FERTILITĂŢII CERNOZIOMULUI PUTERNIC ERODAT ŞI MINIMIZAREA SCURGERILOR DE SUPRAFAŢĂ - USM ADMIN (Studia Universitatis Moldaviae: Stiinte reale si ale naturii, 2010)
Erosion is the main danger of degradation of ecosystems. This phenomenon is less visible and yet existing defined by irreversible destruction of the soil in both organic as well as social consciences. Erosion can be minimized by agrotechnical and phyto-technical methods, which always involve considerable investment. This paper describes several methods for growing perennial grasses that could stop the continuous degradation of soil cover. The annual growth rate of 3 t/ha organic matter in arable layer is assuring a significant increase in fertility, restoring degraded chemical properties of soil erosion and increase the production of herbs. Offset the costs of cultivation technology applied to grasses, constituting 228% organic fertilizer profitability and annual profit amounts 70 lei/ha.